Roosevelt Island: Completing an Urban Community - Kilgore, Karin M. (SURFACE at Syracuse University, 1999)
The thesis became an architectural exploration of what makes neighborhood and community at two scales: at the scale of the city (macrocosm), represented by the urban plan; and at the scale of the individual (microcosm), represented by the concept of the house and housing. At these two contrasting scales, the main focus of the study was to explore how an urban design can shape community and to explore the role that housing plays in the making of urban fabric/neighborhood. These two main issues of urban planning and housing prototypes, and the set of questions they generated, became the framework for the proposed completion of Roosevelt Island's urban structure and housing types. In the end, Roosevelt Island as a site became a very compelling factor in focusing the direction of the investigation, both at the urban planning level, and at the scale of the housing prototypes. At this point, I would like to outline the history of Roosevelt's Island's development before discussing in detail the thesis's urban design proposal and the housing prototype investigation.